Ethical loneliness : the injustice of not being heard - Stauffer, Jill, 1966- (Columbia University Press, 2016)
Ethical loneliness is the experience of being abandoned by humanity, compounded by the cruelty of wrongs not being heard. It is the result of multiple lapses on the part of human beings and political institutions that, in failing to listen well to survivors, deny them redress by negating their testimony and thwarting their claims for justice. In this book, Jill Stauffer examines the root causes of ethical loneliness and how those in power revise history to serve their own ends.